PO 18072 - Peroneus longus tendon injury associated with the presence of peroneum: functional treatment outcome - da Rocha Macedo, Rafael; dos Santos Barroco, Rui; Rodrigues de Miranda, Bruno; Putini, Dario; de Paula Neto, Antônio Candido; Hideki Ikeuti, Douglas; Miller Reis Rodrigues, Luciano (Scientific Journal of the Foot & Ankle, 2019)
Introduction: The os peroneum is a round or oval sesamoid bone located distally within the substance of the peroneus longus tendon near the cuboid bone. Peacock et al. suggested that the presence of the os peroneum might be associated with tendon rupture due to friction at the junction with the bone; in turn, Brigido et al. developed radiographic criteria that associate sesamoid fracture with mechanical failure of the peroneus longus tendon. Objective: To report an unusual case of peroneus longus tendon injury associated with the presence of os peroneum in a patient with hindfoot varus. Methods: A 55-year-old male patient who engaged in physical activity 3 times a week developed pain on the lateral side of the ankle resulting in decreased physical functioning and sports performance. Radiography showed the presence of os peroneum associated with a proximal injury of the peroneus longus tendon detected by magnetic resonance imaging. Results: The patient was treated conservatively with an analgesic physical therapy program followed by functional rehabilitation. The patient progressed from a score of 9 on the visual analog scale for pain in the first month to a score of 0 at 6 months, with grade 5 final eversion force and a return to sports performance at the preinjury level. Conclusion: Treatment options for this injury range from tendon debridement, fixation or excision of the os peroneum to tenodesis or tendon anchorage to the cuboid or calcaneus. Nonsurgical treatment, including immobilization and the use of anti-inflammatory medication, followed by physical therapy is the initial treatment of choice and, as in the reported case, may provide an excellent outcome.